Option selection in whole-body rotation movements in gymnastics - Thomas HEINEN; Marc NICOLAUS (Escola de Educação Física e Esporte da Universidade de São Paulo (EEFEUSP), 2016)
Abstract When a gymnast performs a somersault, the linear and angular momentum along with a particular control of inertia during the flight phase constrain the possibilities for action. Given the complexity and dynamic nature of the human moving system, one could argue that there exist a particular amount of stable coordination states when performing somersaults. The goal of this study was to explore the manifold of movement options and coordination states along with their differentiating parameters for a single somersault in gymnastics based on a simple mathematical model reflecting gymnast's rotation behavior during the flight phase. Biomechanical parameters determining rotation behavior during a somersault were systematically varied with regard to a particular set of biomechanical constraints defining a successful somersault performance. Batch simulations revealed that from 10229760 simulation cycles only 655346 (approximately 6.41%) led to successful somersault performance. A subsequent analysis of the movement option landscape for the optimum angular momentum revealed ten coordination states for a single somersault that could be clearly distinguished based on the simulation parameters. Taken the results together, it becomes apparent that it may be most advisable to perform a single somersault with a larger moment of inertia when achieving the tucked position, a longer duration to achieve the tucked position, a longer duration of staying tucked, and an intermediate moment of inertia during landing. This strategy comprises the largest amount of movement options associated with an upright landing and thus the highest probability of success when performing a single somersault.